The Maximal Lactate Steady State Workload Determines Individual Swimming Performance - Hering, Gernot O.; Stepan, Jens (Frontiers in Physiology, 2021)
The lactate threshold (LT) and the strongly related maximal lactate steady state workload (MLSSW) are critical for physical endurance capacity and therefore of major interest in numerous sports. However, their relevance to individual swimming performance are not well understood. We used a custom-made visual light pacer for real-time speed modulation during front crawl, to determine the LT and MLSSW in a single-exercise test. When approaching the LT, we found that minute variations in swimming speed had considerable effects on blood lactate concentration ([La-]). The LT was characterized by a sudden increase in [La-], while the MLSSW occurred after a subsequent workload reduction, as indicated by a rapid cessation of blood lactate accumulation. Determination of the MLSSW by this so-called “individual lactate threshold” (ILT)-Test was highly reproducible and valid in a constant velocity test. Mean swimming speed in 800 and 1500 m competition (V-Comp) was 3.4% above MLSSW level and V-Comp and the difference between V-Comp and the MLSSW (Δ V-Comp/MLSSW) were higher for long-distance swimmers (800-1500 m) than for short- and middle-distance swimmers (50-400 m). Moreover, Δ V-Comp/MLSSW varied significantly between subjects and had a strong influence on overall swimming performance. Our results demonstrate that the MLSSW determines individual swimming performance, reflects endurance capacity in the sub- to supra-threshold range and is therefore appropriate to adjust training intensity in moderate to severe domains of exercise.